Regulation of Adipose Tissue Inflammation and Insulin Resistance by MAPK Phosphatase 5 - Zhang, Yongliang (J Biol Chem, 2015)
Obesity and metabolic disorders such as insulin resistance and type 2 diabetes have become a major threat to public health globally. The mechanisms that lead to insulin resistance in type 2 diabetes have not been well understood. In this study, we show that mice deficient in MAPK phosphatase 5 (MKP5) develop insulin resistance spontaneously at an early stage of life and glucose intolerance at a later age. Increased macrophage infiltration in white adipose tissue of young MKP5-deficient mice correlates with the development of insulin resistance. Glucose intolerance in MKP5-deficient mice is accompanied by significantly increased visceral adipose weight, reduced AKT activation, enhanced p38 activity, and increased inflammation in visceral adipose tissue when compared with wild-type (WT) mice. Deficiency of MKP5 resulted in increased inflammatory activation in macrophages. These findings thus demonstrate that MKP5 critically controls inflammation in white adipose tissue and the development of metabolic disorders.